MENSTIMULASIKAN KETERAMPILAN MEMBACA PERMULAAN PADA SISWA KELAS III MIN 2 BANDA ACEH MELALUI PENGEMBANGAN MEDIA BIG BOOK - Irwandi (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
students appear less enthusiastic, bored, and pay very little attention to the teacher's explanations. This can be seen from the lack of media use. So the researchers took the title of developing big book media to stimulate initial reading skills in class III MI 2 Banda Aceh students. Because the lack of media use makes students pay less attention to the teacher and have no interest in learning something due to the use of media that is not varied. Therefore, one effort that can be made is to develop big book learning media that can stimulate students' initial reading skills and interest during learning. This research aims to determine the process of developing and determining the feasibility of big book learning media in class III MIN 2 Banda Aceh. The type of research used is Research and Development, which refers to the 4D model which consists of four stages, namely Define, Design, Develop and Disseminate. The instruments used in this research were media expert validation sheets, material validation sheets, teacher response questionnaires. The research results show that: First, the development of big book learning media is very feasible and could be an interesting innovation. Second, the feasibility of big book media was assessed by media experts to get 95% in the